Cybersickness in virtual reality research: A comprehensive bibliometric review and visualisation - Arif Ainur Rafiq; Dwi Sudarno Putra; Mochamad Bruri Triyono; Dian Novian (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2025)
Cybersickness has emerged as a critical challenge in the widespread adoption of virtual reality (VR) technologies across education, healthcare, gaming, and training contexts. As research on cybersickness continues to expand rapidly, a comprehensive mapping of its intellectual structure and research trends is needed. This study aims to systematically analyze the global development of cybersickness research in virtual reality through a bibliometric approach. A total of 1,027 journal articles indexed in the Scopus database, published between 1995 and 2024, were retrieved and analyzed. Bibliometric and visualization techniques were applied using VOSviewer and CiteSpace to examine publication growth, citation patterns, influential authors, leading journals, institutional and country contributions, keyword co-occurrence networks, and citation burst trends. The results reveal a substantial increase in cybersickness-related publications over the past decade, indicating growing scholarly attention driven by advances in VR technology and its broader application domains. Research output is dominated by the fields of computer science, medicine, engineering, psychology, and social sciences. The analysis identifies Virtual Reality and IEEE Transactions on Visualization and Computer Graphics as the most productive journals, while authors such as Stephen Palmisano and Behrang Keshavarz emerge as key contributors. Keyword co-occurrence and timeline analyses highlight evolving research themes, including motion sickness, user experience, head-mounted displays, cognition, and VR exposure. Citation burst detection further indicates a recent shift toward user-centered design and mitigation strategies. Overall, this bibliometric review provides a comprehensive overview of the knowledge structure, research hotspots, and emerging trends in cybersickness research. The findings offer valuable insights for researchers, VR developers, and educators, and serve as a foundation for future interdisciplinary studies aimed at improving user comfort and optimizing VR-based applications.